Thomas mann and the business ethic - Brennan, Joseph Gerard (1985)
Son of a North German businessman, Thomas Mann chose as theme for his early narrative work the conflict between the standards and values of business and those of the artist-writer.Buddenbrooks andTonio Kröger exhibit the tension of values in opposite ways. InThe Magic Mountain, Mann expands his canvas to include military as well as business values in their relation to the creative potential in a young engineer who exiles himself to an Alpine tuberculosis sanatorium to enjoy a unique educational experience. Mann believed that the businessman, like the artist, had a light and dark side, committed by the Protestant ethic, yet bound to entrepreneurial standards of utility and profit. On that account, the businessman, like the creative artist, may experience a certain alientation from ‘Life’.
Keywords: Dark Side; Educational Experience; Business Ethic; Economic Growth; Tuberculosis